Cotton leaf curl Multan virus differentially regulates innate antiviral immunity of whitefly (Bemisia tabaci) vector to promote cryptic species-dependent virus acquisition - Farooq, Tahir; Lin, Qi; She, Xiaoman; Chen, Ting; Li, Zhenggang; Yu, Lin; Lan, Guobing; Tang, Yafei; He, Zifu (Frontiers in Plant Science, 2022)
Begomoviruses represent the largest group of economically important, highly pathogenic, DNA plant viruses that contribute a substantial amount of global crop disease burden. The exclusive transmission of begomoviruses by whiteflies (Bemisia tabaci) requires them to interact and efficiently manipulate host responses at physiological, biological and molecular scales. However, the molecular mechanisms underlying complex begomovirus-whitefly interactions that consequently substantiate efficient virus transmission largely remain unknown. Previously, we found that whitefly Asia II 7 cryptic species can efficiently transmit cotton leaf curl Multan virus (CLCuMuV) while MEAM1 cryptic species is a poor carrier and incompetent vector of CLCuMuV. To investigate the potential mechanism/s that facilitate the higher acquisition of CLCuMuV by its whitefly vector (Asia II 7) and to identify novel whitefly proteins that putatively interact with CLCuMuV-AV1 (coat protein), we employed yeast two-hybrid system, bioinformatics, bimolecular fluorescence complementation RNA interference, RT-qPCR and bioassays. We identified a total of 21 Asia II 7 proteins putatively interacting with CLCuMuV-AV1. Further analyses by molecular docking, Y2H and BiFC experiments validated the interaction between a whitefly innate immunity-related protein (BTB/POZ) and viral AV1 (coat protein). Gene transcription analysis showed that the viral infection significantly suppressed the transcription of BTB/POZ and enhanced the accumulation of CLCuMuV in Asia II 7, but not in MEAM1 cryptic species. In contrast to MEAM1, the targeted knock-down of BTB/POZ substantially reduced the ability of Asia II 7 to acquire and accumulate CLCuMuV. Additionally, antiviral immune signaling pathways (Toll, Imd, Jnk and Jak/STAT) were significantly suppressed following viral infection of Asia II 7 whiteflies. Taken together, the begomovirus CLCuMuV potentiates efficient virus accumulation in its vector B. tabaci Asia II 7 by targeting and suppressing the transcription of an innate immunity-related BTB/POZ gene and other antiviral immune responses in a cryptic species-specific manner.